HASIL BELAJAR KETERAMPILAN SOSIAL FISIKA MELALUI PENDEKATAN KONSTRUKTIVISME PADA SISWA KELAS X1 SMA NEGERI I TAMBANG - Azizahwati Azizahwati; Zulhelmi Zulhelmi; Rahmi Mulyani (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2007)
This aim of the research is to describe result of learning social skill physics student throughapplying strategy learn the constructivism in X1 SMA N class student year 2006/2007 at dynamic electricsdirect material. Research subject is X1 class student consist of 41 people. In this research only selected of 12students at random to be perceived. The instrument of this research consist of study instrument and datacollecting instrument. The collecting data use observation sheet. To analyse data calculated pursuant topresentase from each;every aspect result of learning skill social. From data analysis result of learning skillof highest social to stay in duty equal to 49.16% and lowest percentage of push participation equal to 10.9%.From result of this research can be concluded that passing approach constructivism can make student be incontrol of their given duty.Keyword: result learn skill of social, strategy of konstructivism